Effects of 6-Week Traditional and Functional Resistance Training on Arterial Stiffness and Muscular Strength in Healthy Young Men - Zuo, Chongwen; Li, Qing; Zhang, Li; Bo, Shumin (Frontiers in Physiology, 2022)
Background: The present study investigated the effects of traditional resistance training (TRT) and functional resistance training (FRT) on arterial stiffness and muscular strength in healthy young men. Methods: This randomized controlled trial included 29 untrained healthy young men aged 18–29 years who were randomly divided into two groups, namely TRT group (n = 15) and FRT group (n = 14). All participants underwent numerous tests such as those for body composition, cardio-ankle vascular index, blood pressure, heart rate, and maximal strength before and after the 6-week training program. The exercise training comprised whole-body strength training exercises 3 days a week for 6 weeks. The total training volume and number of sets (4–5 sets) were kept constantly similar in each group. The TRT group completed 4–5 sets of 8–12 repetitions [70% of 1 repetition maximum (1RM)], whereas the FRT group completed 4–5 sets of 15–22 repetitions (40% 1RM). Results: The TRT and FRT groups exhibited equally significantly increased maximal strength (within group: both p < 0.01). Furthermore, the independent t test showed that the differences be-tween the two groups in terms of changes in maximal strength were no significant (between group: both p > 0.05). Additionally, significant main effects of time (pre vs. post) were observed for the left and right cardio-ankle vascular indices (p < 0.05); however, no significant difference were observed between the groups. For body compositions outcome measures, no significant dif-ferences between groups were observed. Conclusions: Six weeks of FRT and TRT exhibit no difference in terms of effects on arterial stiffness and muscular strength.